2020
DOI: 10.7759/cureus.7654
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Sinus Thrombosis in Adults with Prothrombotic Conditions: A Systematic Review and a Case from Our Institution

Abstract: Cerebral venous sinus thrombosis (CVST) is a rare condition characterized by elevated intracranial pressure due to impaired cerebral venous drainage, potentially leading to life-threatening consequences. We searched the PubMed electronic database for 'cerebral venous sinus thrombosis' and 'prothrombotic' cases reported in adults (19+ years) and conducted a systematic review for the published literature in the English language pooled with a case from our institution. Data were analyzed regarding patient demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…13 , 18 Underlying prothrombotic disorder was found in 33.3% of our patients, which is higher than mentioned in some studies (19.8%, 13 26.4%, 16 6.7% 26 ) but in agreement with a study by Ferro et al 14 (34%). 27 We did not find protein C deficiency in any of our patients. Bechet’s disease was found in 25% of cases by Daif et al, 4 9.4% by Duman et al 24 and in none by Kajtazi et al 19 It was found in 2 of our patients, which is similar to a finding by Algahtani et al 13 Infection as the etiology was less frequent than reported in another study from KSA.…”
Section: Discussionmentioning
confidence: 44%
“…13 , 18 Underlying prothrombotic disorder was found in 33.3% of our patients, which is higher than mentioned in some studies (19.8%, 13 26.4%, 16 6.7% 26 ) but in agreement with a study by Ferro et al 14 (34%). 27 We did not find protein C deficiency in any of our patients. Bechet’s disease was found in 25% of cases by Daif et al, 4 9.4% by Duman et al 24 and in none by Kajtazi et al 19 It was found in 2 of our patients, which is similar to a finding by Algahtani et al 13 Infection as the etiology was less frequent than reported in another study from KSA.…”
Section: Discussionmentioning
confidence: 44%
“…Therefore, the clinician must have a high suspicion for diagnosis if a patient presents with a headache and has one or more known risk factors for CVST [4,10]. This case illustrates how in those without typical or previously identified risk factors, a comprehensive investigation through a detailed history, physical examination including ophthalmoscopic examination, and pertinent laboratory studies under most recent guidelines are warranted [4,9,10].…”
Section: Discussionmentioning
confidence: 98%
“…The presentation of CVST is highly variable; however, it commonly presents with at least one of a few symptoms. The most common presenting symptoms include headache, focal neurological deficits, and seizures [4,5,9]. Headache is by far the most common, with 70% to 90% of patients presenting with this symptom [4,9,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations